The impact of China’s employee basic medical insurance outpatient pooling scheme on outpatient healthcare utilization among middle-aged adults - Xinjuan Zhou; Xinrui Li; Haiyi Chen; Jing Deng (PLoS ONE, 2026)
Background This study evaluates the association between China’s Employees’ Basic Medical Insurance (EBMI) outpatient pooling policy and outpatient service utilization among middle-aged insured individuals (aged 45–60). By analyzing outpatient service use, visit frequency, and out-of-pocket (OOP) expenditures, the study documents utilization patterns associated with the policy and explores their implications for healthcare-seeking behavior among middle-aged enrollees, providing evidence that may inform future adjustments to outpatient coverage design. Methods Using cross-sectional data from the 2018 wave of the China Health and Retirement Longitudinal Study (CHARLS), this study employed a logistic regression model to examine the effect of the outpatient pooling policy and different levels of outpatient benefit coverage on the probability of outpatient visits. A zero-inflated negative binomial regression model was used to analyze the impact on the frequency of outpatient visits, and a Tobit model was applied to assess its effect on out-of-pocket outpatient expenditures. Although the analysis relies on 2018 pilot data, the core institutional mechanisms of outpatient pooling were retained in the post-2021 national framework, suggesting that behavioral responses observed in pilot regions may still be informative under the current reform framework. Results Implementation of the outpatient pooling policy was associated with a 5.0 percentage points higher probability of outpatient visits ( p < 0.05) and a significantly higher visit frequency (IRR = 1.80, p < 0.01). Predictive estimates indicate that expected out-of-pocket expenditure in policy regions was approximately 48% higher than in non-policy regions ( p < 0.05). Regions with higher levels of outpatient benefit coverage exhibited stronger utilization responses. In addition, individuals with multiple chronic conditions demonstrated significantly greater outpatient healthcare utilization. Conclusions The EBMI outpatient pooling policy was associated with higher outpatient service utilization, suggesting improved access to previously unmet outpatient healthcare needs. However, additional adjustments may be required to better address the needs of patients with chronic conditions and to strengthen primary healthcare resources, thereby contributing to improvements in equity and efficiency.